Synthesis and Magneto-Spectral Properties of Co(II), Ni(II), Cu(II) Complexes with 4-Methyl Isonitrosoacetophenone - Raut, R.D.; Patil, M.R. (Asian Journal of Chemistry, 2010)
Studies of the complexes of transition metal ions with 4-methyl isonitrosoacetophenone (HIMAP) have been carried out on the basis of elemental analysis, molar conductance electronic spectra etc. The complexes have been assigned the formula M(IMAP)2 (M = Co, Ni or Cu).